Does Public Debt Affect Economic Growth? An Empirical Investigation of Upper-Middle-Income Countries - Nurhanifah, Nita Viviani; Hartarto, Romi Bhakti; Dewanti, Diah Setyawati (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149)DO - 10.24843/JEKT.2025.v18.i01.P01, 2025)
Public debt has increased dramatically over the past few decades. The emergence of budget crises in developing countries has led to this phenomenon. Using panel data from 2013 to 2022, this study investigates the impact of public debt on economic growth in 11 upper-middle-income countries. The panel data regression model was estimated using the fixed effect model. The findings show that public debt has a significant and positive impact on economic growth. Therefore, the government must cut back on public debt procurement, implement structural reforms, and establish a credible regulatory framework to ensure long-term economic growth and debt sustainability.